Analysis of errors in endodontic treatment according to cone-beam computed tomography - E. P. Zinkovskaya; E. V. Chestnykh; L. A. Goreva; I. O. Larichkin; N. V. Shedyakova; E. L. Zakharova (Эндодонтия Today, 2024)
AIM. The aim of the study was to study the frequency of errors in endodontic treatment according to cone beam computed tomography.MATERIALS AND METHODS. 71 cone beam computed tomography (CBCT) scans of patients treated by random sampling who sought treatment and consultation in the period 2022–2023 were studied. 256 teeth previously subjected to endodontic treatment with the presence or absence of radiological signs of chronic apical periodontitis were examined. The assessment of the quality of root canal obturation and the features of the anatomical structure of teeth was carried out. The data of the «Ray RAYSCAN alpha 3D» cone beam computed tomograph were studied using the OnDemand3DDental program. The results were considered statistically significant at p< 0.05.RESULTS. In 57.42% of cases, there were no signs of periapical pathology, and in 42.58%, foci of bone destruction in the periapical region were observed. Homogeneously, 58.59% of root canals were sealed to the apex. In 16.79% of cases, the removal of filling material outside the root canal was noted. 10.54% of teeth with insufficient root canal filling depth and 6.64% of teeth with a missing root canal were also identified.CONCLUSIONS. There is a decrease in the incidence of the most common errors of endodontic treatment. The method of cone beam computed tomography is important at the stage of diagnosis and planning of endodontic treatment to assess the features of the internal structure of the tooth.